Bribes and local fiscal autonomy in Russia. - Pertti Haaparanta; Tuuli Juurikkala (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
Russian industrial enterprises inherited from the Soviet era a tradition of producing welfare and infrastructure services within the firm, also for outside users. Despite the massive restructuring of the economy that took place since, many firms are still active in service provision. At the same time, opaque fiscal federalism is a problem for municipalities whereas rent extraction by public sector officials is a problem for firms. In this paper we examine whether there is a link between these phenomena. We propose a model on local fiscal incentives, service provision by firms and the municipality-firm relationship in the form of bribes. Using survey data from 404 medium and large industrial enterprises in 40 regions of Russia, we find that the higher the share of own revenues in the local budget, the more likely the firms are to report bribes. In the case of infrastructure services, the data also support the hypothesis that the channel is through service provision: the less fiscal autonomy, the more service provision and the less likely the firms are to report bribes.
URN:NBN:fi:bof-201408071920
Keywords: 330